742 Quality of Operative Notes for Renal Transplant Surgery - Is Our Documentation Satisfactory?. (19th August 2022) - Gupta, S; Mahesh, S; Koimtzis, G; Chalklin, C; Ilham, MA; Elker, D; Stephens, MR; Khalid, U
Abstract: Introduction: Operation notes are essential in providing details of the procedure undertaken. The Royal College of Surgeons (RCS) Good Surgical Practice (GSP) guidelines recommend a checklist of 18 documentation items. Although these guidelines are useful, their broad and non-specific nature provides limitations to fields like transplantation, where additional information is needed. Ghoneima et al recommended transplant specific GSP checklist of 32 criteria for operation notes in transplantation. Our aim is to evaluate renal transplantation operation notes against these criteria. Method: A retrospective audit of renal transplant operation notes was undertaken within Cardiff Transplant Unit between October 2020–2021. Notes were reviewed against new transplant specific GSP checklist. Results: A total of 85 renal transplants were performed by 8 Consultant Surgeons. Sixty-two (73%) operation notes were hand-written and 23 (27%) electronically typed. Eleven standards had documentation compliance of >95% (e.g., date, surgeons' names, recipient blood vessels, incision, allograft vascular anatomy, perfusion timings, closure, signature, etc). Some important transplant-specific information (e.g., primary renal disease, details of current renal replacement therapy, reperfusion characteristics, donor details (e.g., age, comorbidities), HLA mismatch, prosthesis (ureteric stent) details) were poorly documented (0–27% documentation compliance). Antibiotic and DVT prophylaxis documentation was also very poor (1–30%). Post-operative instructions did not record target blood pressure (0%) and postoperative potassium and ultrasound scan instructions were recorded in 65% of notes. Discussion: Clear documentation is important for good surgical practice. This study highlights the need for a transplant-specific operation notes template, to not only improve the documentation but to standardize the key information recorded for every transplant performed.